Edge-Enabled UAVs for Last Mile Delivery with Reliable Data Transmission in IoV Networks for Healthcare and Emergency Service - Chakravarthy R, Arun; M, Arun; C, Sureshkumar (Journal of Neonatal Surgery, 2025)
This paper presents a comprehensive framework for improving the performance of Unmanned Aerial Vehicles (UAVs) in last mile delivery applications, particularly within the domains of healthcare and emergency response. By integrating edge computing into UAV architecture, the system facilitates real-time data processing at the network edge, significantly reducing latency and enhancing decision-making capabilities during critical operations. The proposed model addresses the increasing demand for fast, autonomous delivery of medical supplies and emergency resources in both urban and remote settings. To ensure uninterrupted communication and data reliability, the system leverages Internet of Vehicles (IoV) networks alongside robust transmission protocols that enhance connectivity between UAVs, edge devices, and command centers. This integration enables consistent and accurate data exchange, even under challenging network conditions. The approach enhances the overall responsiveness, efficiency, and dependability of UAV-based delivery systems, offering a scalable solution for intelligent transportation in mission-critical healthcare scenarios.